Anconeus epitrochlearis muscle (epitrochlearisanconeus muscle; Musculus epitrochleoanconeus) with cubital tunnel syndrome – a rare but relevant clinical entity - Grüner, Jasmin; Paulsen, Friedrich; Barth, Anna; Horch, Raymund E. (Annals of Anatomy-Anatomischer Anzeiger, 2023)
Background: Compression of the ulnar nerve at the elbow within the cubital tunnel is related to the anatomical structures and is generally believed to be caused by Osborne's ligament (also known as the cubital retinaculum). However, in rare cases an anatomical variation of the developmental peculiarity of a remaining anconeus epitrochlearis muscle may be responsible for the disease. Methods: We present a series of five cases in which an anconeus epitrochlearis muscle was found as the cause of illness. Results: All patients presented with typical symptoms of numbness and tingling in the hand and ulnar fingers, and recurring pain as well as weakness of the ulnar innervated muscles. With neurophysiologically confirmed diminished nerve conduction velocity and unsuccessful conservative treatment, surgical decompression revealed an anconeus epitrochlearis muscle as the reason of compression. Full symptom relief was achieved immediately after the procedure in all cases. Conclusions: This article strives to call attention to this entity when diagnosing ulnar nerve compression. Myectomy and medial epicondylectomy is the preferred treatment option in such cases.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Cubital tunnel syndrome; Musculus anconeus epitrochlearis; Musculus epitrochleoanconeus; Sulcus ulnaris